The Effect of Compensation on Employee Performance at PT. Sango Indonesia - Karawang - Agung Surya Dwianto; Rustomo Rustomo; Andri Aprurroji (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2019)
Employee performance is very important for the achievement of the goals of a company. One important factor that can affect performance in a company is from providing compensation given to employees. Compensation is something that is received by employees as a substitute for their service contribution to the company. The existence of a good compensation system will ensure the occurrence of justice between employees and the company. Each employee will receive a reward in accordance with the goals, functions, positions, and work performance Compensation problems are a sensitive problem because they are driving people to work hard. Besides that compensation also affects morale and labor discipline. Therefore, any company / organization should be able to provide compensation that is balanced with the workload borne by the workforce. This research was conducted at PT. Indonesian Sango. The purpose of this study was to determine the effect of compensation on the performance of employees at PT. Indonesian Sango. PT. Sango Indonesia is a company engaged in the Automotive Part that produces Secondary Steel and Exhaust Manifold. Shareholders in PT. Sango Indonesia is divided into Sango Group, Toyota Thuso, Sumitomo Corporation, sumitomo corporation Indonesia and shinsho corporation. Meanwhile, the purpose of this study was to determine the effect of compensation on the performance of employees at PT. Indonesian Sango. Based on the results of the study it can be seen that Compensation has a contribution of influence of 50.83% on the performance of employees of PT. Indonesian Sango. While the remaining 49.17% is influenced by other factors. From the results of the study it can be concluded that compensation is needed to help strengthen the organization's key values ​​and facilitate the achievement of organizational goals Keywords: Compensation, Employee